(untitled) (Journal of Fiber Bioengineering and Informatics, 2019)
The inkjet printing technique has been rapidly developing for the realization of flexible electronic devices. The antennas, sensors and transistors have been successfully introduced on flexible substrates such as glass, silicone and many films. Since the inkjet printing technique is a direct writing process, the benefits include flexible design, low-cost and environmentally friendly. It is also possible to create a high resolution of printed lines. Therefore, this technique is believed to have a great potential for applying on textile substrates. However, the challenge is to ensure that the small droplets can penetrate through the thickness of the fabric in order to spread along the threads. Thus, the uniformity and continuity are not acceptable for practical applications. This paper summarises inkjet printing technologies and potential applications on textile substrates.